ИНТЕРНЕТ ВЕЩЕЙ (IOT): ЛИТЕРАТУРНЫЙ ОБЗОР - Сайманов, И.М. (SCIENCE and SOCIETY, 2021)
One of the most prestigious words in information technology is the Internet of Things (IoT). The future belongs to the IoT, which will turn objects of the real world into mental virtual objects. The IoT wants to bring everything in our world together in a collaborative infrastructure, giving us not only control over things around us, but also keeping us informed about the state of things. In light of this, a genuine study explores the concepts of the Internet of Things through periodic review of scientific studies, corporate white papers, professional discussions with experts, and online databases. Apart from that, this research article focuses on definitions, genes, main claims, traits and pseudonyms of the Internet of Things. The main task of this article is to provide an educational program for the Internet of Things, architectures and relevant technologies and their application in our everyday life. Not least, this manuscript will work as a good awareness for fresh explorers who wish to conduct studies in this area of the Internet of Things (Technological God) and contribute to the effective accumulation of knowledge.
Keywords: Internet of Things; IoT; RFID; IPv6; EPC; Barcode; Wi-Fi; Bluetooth; NFC; ZigBee; Sensors; Actuators